FOCUSING THE CONTENT OF ARTICLES, YET NEGLECTING THE CITATION AND REFERENCE STYLE - Setiarini, Ni Luh Putu Putu (Journal of Language and Literature, 2021)
Scholars tend to give extra efforts to write the content of their study, yet some forget to pay much attention in writing the standardization of citation and reference. It yields errors in presenting citation and reference based on the guideline required by the journals. Citing and referencing are two mediums to quote authors’ opinions and also give credits for their intellectual ideas. An analysis of citation and reference of articles indexed by Scopus Quartile 2 was carried out to scrutinize errors in writing citation and reference page. The data were taken from a journal required authors to adhere the guidelines of the Publication Manual of the American Psychological Association (7th Ed). The method used was qualitative. The data of 68 errors in citations and 139 errors in reference page were gathered by downloading the articles from the website of the journal. The results show that errors identified in writing the citation are classified into narrative citation and parenthetical citation. Errors vary in initiating page number, incorrect use of ampersand, incorrect style of multiple citation and wrong order of multiple citations. With regard to reference page, errors are detected in writing the titles of the works, typing the references taken from journals and proceedings and no translation provided from other languages. Errors in referencing edited works and abbreviating the authors are also pinpointed. The results imply that in order to produce accurate citations and references, authors are obliged strictly to follow and conform one style required by the journal